2019
DOI: 10.1038/s41598-019-43268-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure and stability of the coral microbiome in space and time

Abstract: Although it is well established that the microbial communities inhabiting corals perform key functions that promote the health and persistence of their hosts, little is known about their spatial structure and temporal stability. We examined the natural variability of microbial communities associated with six Caribbean coral species from three genera at four reef sites over one year. We identified differences in microbial community composition between coral genera and species that persisted across space and tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 71 publications
2
65
0
Order By: Relevance
“…The host, environment, and time can influence the microbiome composition [26]. However, in general, the host is the most significant factor influencing the microbial community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The host, environment, and time can influence the microbiome composition [26]. However, in general, the host is the most significant factor influencing the microbial community.…”
Section: Discussionmentioning
confidence: 99%
“…Purported to enhance the hosts' fitness and functioning [17], the coral microbiome is the central part of a widespread hypothesis of co-evolutive processes known as holobiont [18,19]. Taking into account factors such as location, environmental changes, depth, bleaching, and diseases, the microbiome of more than 30 coral species has already been studied [20][21][22][23][24][25][26]. Focusing on Bacteria, it is suggested that Proteobacteria, Bacteroidetes, Firmicutes, Actinobacteria, and Cyanobacteria are predominant [20] and that their diversity and abundance are linked to biotic and abiotic factors such as seasonality, anthropic impacts, temperature changes, diseases, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The mucus was strongly influenced by environmental factors, while the skeleton microbiome was the most diverse and most likely to show phylogenetic structure, reflecting the influence of host traits. The influence of phylosymbiosis, defined as "microbial community relationships that recapitulate the phylogeny of their host" (Brucker and Bordenstein, 2013), was higher than regional dispersal or environmental heterogeneity and differed across anatomy, being stronger in the skeleton than in tissue or mucus (Pollock et al, 2018;Dunphy et al, 2019). Regarding the prevalence of spatial structure, Pollock et al (2018) showed that the external mucus microbiome is 1.15-fold more influenced by collection site than coral tissue and 1.28-fold more than skeleton communities (Pollock et al, 2018).…”
Section: Coralsmentioning
confidence: 99%
“…The spatial structure of coral microbiomes could be influenced by regional processes including dispersal limitation and spatiotemporal environmental heterogeneity even at small spatial distances (Dunphy et al, 2019). Nevertheless, these spatial differences are limited in comparison to differences between coral genera or species (Dunphy et al, 2019).…”
Section: Coralsmentioning
confidence: 99%
“…Microbial symbionts in reef-building corals, which support a variety of marine life, reside in the mucus, tissue, and skeleton of diverse corals, influencing health of its host coral (1, 2). Microbial symbionts comprise bacteria, archaea, algae, fungi, and viruses, and their composition is influenced by their host corals’ genetic factors and dynamic environmental conditions (3). They can help corals prevent or mitigate diseases and benefit corals by involving them in carbon, nitrogen, and sulfur cycles (4).…”
Section: Introductionmentioning
confidence: 99%